The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3382/ps/pex139
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal microbial population of turkey (Meleagris gallopavo) affected by hemorrhagic enteritis virus

Abstract: Hemorrhagic enteritis (HE) is an acute viral disease that affects avian species, particularly turkeys, compromising their commercial production and having a negative effect on animal welfare. Turkey adenovirus 3 (TAdV-3), is the main causal agent of the disease. In this study, we considered 3 groups of turkeys to achieve 2 purposes: 1) A preliminary investigation on the microbiota content in the 4 parts of healthy turkey's intestine (group A), namely duodenum, jejunum, ileum, and ceca was done; 2) an investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…In agreement with results from previous studies in broilers (45), turkeys (46), geese (47), and laying hens (48), the present study revealed that the core phyla within the cecal microbiota, regardless of treatments and phases (grower, developer, and laying phase), were primarily Firmicutes and Bacteroidetes. Despite the lack of difference in the relative abundance of bacterial communities at the phylum level between treatments, distinct differences were evident at lower taxonomic levels, mainly at the genus level, despite their low relative abundance.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with results from previous studies in broilers (45), turkeys (46), geese (47), and laying hens (48), the present study revealed that the core phyla within the cecal microbiota, regardless of treatments and phases (grower, developer, and laying phase), were primarily Firmicutes and Bacteroidetes. Despite the lack of difference in the relative abundance of bacterial communities at the phylum level between treatments, distinct differences were evident at lower taxonomic levels, mainly at the genus level, despite their low relative abundance.…”
Section: Discussionsupporting
confidence: 92%
“…As for the spatial distribution, distinct microorganisms prefer different gastrointestinal sections [ 29 , 31 , 33 ]. For example, Bacteroidetes was found to be considerably more abundant in the cecum than in the other intestinal sections of quail, with similar trends observed in previous reports on Japanese quail [ 6 ], turkeys [ 34 ], chickens [ 29 ] and geese [ 31 ]. At the genus level, Lactobacillus was dominant in the duodenum, jejunum, ileum, and colorectum, while being remarkably reduced in the cecum, where Faecalibacterium , Bacteroides , Alistipes , Parabacteroides , and Anaerostipes were notably increased, consistent with the genera distribution found in Japanese quail [ 6 ] and our previous findings on broiler chickens [ 29 ] and geese [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…The characterization of gut bacteria in several studies reveals a dominance of Firmicutes and Bacteroidetes, which appears to be a common feature of birds. The dominance of these phyla has been described in the ceca of turkeys (Meleagris gallopavo) [23], the cloacal samples of Chinstrap penguins (Pygoscelis antarctica) [24], the feces of Japanese quail (Coturnix japonica) [25], as well as in the crop of hoatzin (Opisthocomus hoazin) [26]. However, previous studies also reported that Proteobacteria and Firmicutes are the dominant phyla in the feces of macaroni penguins (Eudyptes chrysolophus), little blue penguins (Eudyptula minor) [27], Procellariiform seabirds [28], Lady Amherst's pheasant (Chrysolophus amherstiae), Reeves's pheasant (Syrmaticus reevesii), and Cabot's tragopan (Tragopan caboti) [29], which is more consistent with our observations of the microbiota composition in the Chinese monal.…”
Section: Discussionmentioning
confidence: 99%